Iowa RBA, July 14, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for July 14, 1997. Highlights of the update include sightings of a Scissor-tailed Flycatcher, a King Rail, a first year Sabine's Gull, Piping Plovers, and Least Terns. Also included are handwritten notes for the next week's update with sightings of a Snowy Egret, a pair of Least Bitterns, and a Northern Mockingbird. Epson - sheet feed/flatbed